2021
DOI: 10.1111/chso.12454
|View full text |Cite
|
Sign up to set email alerts
|

Children, language and access to schools in the global South: The case of migrants in Ghana

Abstract: Research on migrant children and young people has often focused on the global North and less on South-South migration. This article discusses language and its effect on how young migrants access Ghanaian schools. Through interviews with 68 pupils, 21 parents and 40 teachers and principals from 30 schools across Accra, we found that children and young people from francophone countries were placed in lower than age-appropriate grades due to their lower command of English. Our study highlights the complex linguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Many teachers did not think lower proficiency in English was peculiar to only migrant children considering the multilinguistic and multicultural Ghanaian context where students were taught in a language other than their mother tongue. This phenomenon is not limited to Ghana but a common feature of postcolonial countries in sub-Saharan Africa (Kyereko and Faas 2021). This finding is in stark contrast from most research (see Arnot, Schneider, and Welply 2013;Rodríguez-Izquierdo and Darmody 2019) on migrant education in countries in the global North.…”
Section: Teaching Migrant Children In Ghanaian Schoolsmentioning
confidence: 59%
“…Many teachers did not think lower proficiency in English was peculiar to only migrant children considering the multilinguistic and multicultural Ghanaian context where students were taught in a language other than their mother tongue. This phenomenon is not limited to Ghana but a common feature of postcolonial countries in sub-Saharan Africa (Kyereko and Faas 2021). This finding is in stark contrast from most research (see Arnot, Schneider, and Welply 2013;Rodríguez-Izquierdo and Darmody 2019) on migrant education in countries in the global North.…”
Section: Teaching Migrant Children In Ghanaian Schoolsmentioning
confidence: 59%
“…Further factors that have been shown to influence migrant children's schooling experiences and outcomes include teachers' lacking pedagogical competency to teach in diverse classrooms, language differences between teachers and students (McGinnity, Darmody and Murray, 2015;Ní Dhuinn and Keane, 2021), the lack of migrants' identification with host cultures (Sheikh and Anderson, 2018) and "the lack of psychological support available for students and parents who experience racists incidents and bullying" (Stylianou, 2017, p. 997). The relevance of language competency for academic achievement was also demonstrated in a Ghanian study (Kyereko and Faas, 2021) which found that francophone migrant students in an anglophone Ghanian school were placed in lower-age grades due to their poor comprehension of English.…”
Section: Migrant Families' Transitions In/to New Education Systems -I...mentioning
confidence: 83%
“…These challenges are not peculiar to the Irish context. Evidence shows that migrant families in other countries in the Global North and Global South encounter similar challenges (Baysu et al, 2021;Gabrielli and Impicciatore, 2021;Kyereko and Faas, 2021;Ngo, 2008). We, therefore, argue for specific support programmes and policies to assist migrant families and their children as they settle in Ireland.…”
Section: Discussionmentioning
confidence: 94%
“…Further, a number of articles consider the shaping of language by sociocultural context and psychosocial processes (Crafter & Iqbal, 2021; Phoenix & Faulstich Orellana, 2021; Romero‐Moreno & Vargas‐Urpí, 2021). Articles are drawn mainly from the Global North; Kyereko and Faas (2021) in describing their Ghanaian research suggest some similar issues in the Global South but highlight the complex nature of linguistic barriers in the post‐colonial world.…”
Section: Overviewmentioning
confidence: 99%
“…Additionally, many of the authors share an interest in policy implications, entering into educational debates on how to support indigenous languages, the potential of place‐based and language‐awareness approaches (Cohen & Rønning, 2021), translanguaging (Peace‐Hughes, 2021), and on the impact of ineffective language policy on educational outcomes (Horgan et al, 2021; Kyereko & Faas, 2021).…”
Section: Overviewmentioning
confidence: 99%